2012
DOI: 10.1177/1471301212456277
|View full text |Cite
|
Sign up to set email alerts
|

Reminiscence in dementia: A concept analysis

Abstract: This paper is a report of an analysis of the concept of reminiscence in dementia and highlights its uses as a therapeutic intervention used on individuals with dementia. No single definition of reminiscence exists in healthcare literature; however, definitions offered have similar components. The term life review is commonly used when discussing reminiscence; however, both terms are quite different in their goals, theory base and content. This concept analysis identified reminiscence as a process which occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 63 publications
(190 reference statements)
0
73
0
2
Order By: Relevance
“…Our results also supported the hypothesis that caregivers in the MRT groups perceived a greater positive experience than those who did not. Reminiscence therapy helps people to reassess their past life experiences, maintain their self‐value and self‐identification, promotes the interactions between people, and encourages people to prepare for their future . Reminiscence therapy works by improving positive experiences, including both self‐affirmation and an individual's outlook on life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also supported the hypothesis that caregivers in the MRT groups perceived a greater positive experience than those who did not. Reminiscence therapy helps people to reassess their past life experiences, maintain their self‐value and self‐identification, promotes the interactions between people, and encourages people to prepare for their future . Reminiscence therapy works by improving positive experiences, including both self‐affirmation and an individual's outlook on life.…”
Section: Discussionmentioning
confidence: 99%
“…Reminiscence therapy helps people to reassess their past life experiences, maintain their self-value and self-identification, promotes the interactions between people, and encourages people to prepare for their future. 38 and enhances the ability to plan for future goals. 39 A meta analysis of the effects of RT 40 indicated that its use could improve mental health, the ability to self-improve, positive happiness, sense of control, and the ability to blend into society.…”
Section: Discussionmentioning
confidence: 99%
“…The OLSB utilizes the natural process of recollecting memories and stimulates this process. It is known that in an early stage of dementia, people can still retrieve and share memories from the past [13, 14]. However, our research focuses on a relatively short time period of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, reminiscence interventions are part of the Dutch standard for dementia care [12]. Personal memories belong to the autobiographical memory system, a part of memory that remains intact in dementia for a relatively long time [13, 14]. Most persons with early dementia are able to retrieve personal memories and share them.…”
Section: Introductionmentioning
confidence: 99%
“…Reminiscence is a vital part of the aging process which can help older adults achieve ego integrity . Older adults with mild dementia tend to retain vivid memories of the distant past which they may be able to retrieve during reminiscence activities . Reminiscence in the care of people with mild dementia is classified as an independent nursing intervention that can be utilized in a variety of settings to address psychosocial problems associated with dementia .…”
Section: Introductionmentioning
confidence: 99%